1987
DOI: 10.1123/ijsb.3.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Upper Extremity Function in Running. II: Angular Momentum Considerations

Abstract: Ten male recreational runners were filmed using three-dimensional cinematography while running on a treadmill at 3.8 m/s, 4.5 m/s, and 5.4 m/s. A 14-segment mathematical model was used to examine the contributions of the arms to the total-body angular momentum about three orthogonal axes passing through the body center of mass. The results showed that while the body possessed varying amounts of angular momentum about all three coordinate axes, the arms made a meaningful contribution to only the vertical compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 5 publications
5
73
1
Order By: Relevance
“…During running the angular momentum about a vertical axis of the upper trunk and arms has been shown to be opposite to the angular momentum about a vertical axis of the lower extremities (Hinrichs, 1987). It is therefore likely that the kinematic pattern for axial rotation of the lumbar spine during running is a reflection of the angular momentum about a vertical axis of the upper trunk and arms developed to directly counteract the angular momentum about a vertical axis of the reciprocally swinging lower extremities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During running the angular momentum about a vertical axis of the upper trunk and arms has been shown to be opposite to the angular momentum about a vertical axis of the lower extremities (Hinrichs, 1987). It is therefore likely that the kinematic pattern for axial rotation of the lumbar spine during running is a reflection of the angular momentum about a vertical axis of the upper trunk and arms developed to directly counteract the angular momentum about a vertical axis of the reciprocally swinging lower extremities.…”
Section: Discussionmentioning
confidence: 99%
“…Wiklander, Lysholm, and Lysholm (1987) reported a significant negative correlation between the degree of pelvic obliquity and the flexibility of the hamstrings. Interestingly, this group of investigators found that distance runners in comparison to sprinters had stiffer hamstrings, greater pelvic obliquity and suffered more exertion injuries around the lower back (Lysholm, Gillquist, & Nordin, 1982;Lysholm & Wiklander, 1985, 1987Wiklander et al, 1987). In order to verify any of these proposed relationships, an understanding of the typical kinematic patterns of the lumbar spine and pelvis during running is clearly the crucial starting point.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, removing the arms could lead to compensatory strategies that exact a metabolic cost. As Hinrichs (Hinrichs, 1987) discovered, the momentum effects of arm swing are due to the relatively longer distance of the arm's COM from the vertical axis, acting to generate the largest component of the vertical angular momentum of the entire upper body, which includes the head and trunk. Although the momentum effects of arm swing reduce the amount of torso rotation, there is likely a small cost resulting from the tonic muscular activity required to hold the arms in a flexed position at the elbow, a common style of swinging the arms during human running.…”
Section: Research Articlementioning
confidence: 99%
“…Both Hinrichs (Hinrichs, 1987) and Hamner et al (Hamner et al, 2010) identified that the primary function of arm swing during distance running is to counterbalance the angular momentum generated by the swinging legs about the vertical axis, resulting in a net vertical angular momentum that fluctuates with a relatively low magnitude about zero. Much earlier, Hopper (Hopper, 1964) speculated that in addition to helping maintain posture and balance, arm swing might assist with increasing the vertical ground reaction force to lift the runner, thus bouncing off the ground more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Our arms tend to swing out of phase with our legs, the right arm swinging forward with the left leg and vice versa. Although it has long been established that the arms do not swing as simple, unrestrained pendulums (Elftman, 1939;Fernandez Ballesteros et al, 1965;Jackson et al, 1978;Hinrichs, 1987;Ohsato, 1993;Webb et al, 1994;Gutnik et al, 2005), the extent to which the shoulder muscles actively drive the arms, and the effect of arm swing on stability and economy during walking and running are poorly understood. In this paper, we examined the control of arm swing during walking and running, and investigated the effect of restricting arm swing on stability and metabolic cost.…”
Section: Introductionmentioning
confidence: 99%